Mps1 regulates kinetochore-microtubule attachment stability via the Ska complex to ensure error-free chromosome segregation - Maciejowski, John (Dev Cell, 2017)
The spindle assembly checkpoint (SAC) kinase Mps1 not only inhibits anaphase but also corrects erroneous attachments that could lead to missegregation and aneuploidy. However, Mps1’s error correction-relevant substrates are unknown. Using a chemically tuned kinetochore-targeting assay, we show that Mps1 destabilizes microtubule attachments (K-fibers) epistatically to Aurora B, the other major error-correcting kinase. Through quantitative proteomics, we identify multiple sites of Mps1-regulated phosphorylation at the outer kinetochore. Substrate modification was microtubule-sensitive and opposed by PP2A-B56 phosphatases that stabilize chromosome-spindle attachment. Consistently, Mps1 inhibition rescued K-fiber stability after depleting PP2A-B56. We also identify the Ska complex as a key effector of Mps1 at the kinetochore-microtubule interface, as mutations that mimic constitutive phosphorylation destabilized K-fibers in vivo and reduced the efficiency of the Ska complex’s conversion from lattice diffusion to end-coupled microtubule binding in vitro. Our results reveal how Mps1 dynamically modifies kinetochores to correct improper attachments and ensure faithful chromosome segregation.